Urban ecocriticism and Kolkata's metamorphosis: a narrative exploration of environmental crisis in Jhumpa Lahiri's the lowland - Akhter, Zaid; Islam, Md. Sahidul (Penerbit Universiti Kebangsaan Malaysia, 2024)
The lowland unfolds against the backdrop of a rapidly transforming Kolkata, where unchecked industrialisation and urbanisation have significantly impacted the city's ecosystem. The study delves into the theory of "Urban Ecocriticism", which examines the intersection of literature, cities, and the environment. The focus is on Kolkata, known as the "City of Joy," and how it is changing due to increased population and demands for resources. The novel serves as evidence of Kolkata's environmental crisis as a symptom of broader societal issues, highlighting themes of environmental justice, sustainability, and the need for alternative development models. This paper posits that Lahiri's depiction of Kolkata's transformation is intricately linked to the environmental challenges experienced by the metropolis. This study employs the framework of urban ecocriticism to assess how pollution, the loss of green areas, and the depletion of natural resources are represented in the novel as effects of urbanisation on Kolkata's ecosystems. The discussion connects the novel's local concerns to global conversations about urban ecology and the fight for a more just and sustainable future. The paper investigates the impact of urbanisation on the city's ecological balance and analyses the author's portrayal of the consequences of rapid development on the natural environment. In addition to describing the city and its surroundings, the study also discusses how infrastructure development threatens nature. The study suggests how a work of fiction can also aid in understanding the actual environmental changes taking place in a metropolis like Kolkata.